PERAN KELOMPOK SADAR WISATA (POKDARWIS) DALAM PENGEMBANGAN POTENSI PARIWISATA (STUDI KASUS DI DESA KAMPUNG TAHU KECAMATAN DOLOK MASIHUL KABUPATEN SERDANG BEDAGAI) - Trisnawaty, Trisnawaty (Akademi Pariwisata Darma Agung, 2023)
This study aims to explore the role of Tourism Awareness Groups (POKDARWIS) in developing tourism potential in Kampung Tahu Village, Dolok Masihul District, Serdang Bedagai District. The research method used is a qualitative method with a case study approach. The results showed that POKDARWIS has an important role in developing tourism potential in Kampung Tahu Village. POKDARWIS carries out various activities to develop tourism potential, such as promoting existing tourist objects, fostering and training the community as tour guides, and collaborating with related parties. In addition, POKDARWIS also plays a role in preserving the culture and environment around tourist objects. Through the activities carried out, POKDARWIS is able to increase the number of tourist visits and provide economic benefits for the local community. However, there are also several obstacles faced by POKDARWIS in developing tourism potential, such as a lack of support from the government and a lack of adequate tourism support facilities. Therefore, POKDARWIS needs support from related parties to continue to develop tourism potential in Kampung Tahu Village.